The Kubernetes bible the definitive guide to deploying and managing Kubernetes across cloud and on-prem environments - Madapparambath, Gineesh; McKendrick, Russ (Packt Publishing Ltd., 2024)
Kubernetes has become the go-to orchestration platform for containerized applications. As a Kubernetes user, you know firsthand how powerful yet complex this tool can be. The Kubernetes Bible cuts through the complexity, offering hands-on examples and expert advice to conquer containerization challenges. With this new edition, you will master cutting edge security practices, deploy seamlessly and scale effortlessly, ensuring unwavering service availability. You will gain the expertise to craft production-grade applications, secure development environments, navigate complex deployments with ease, and become a security maestro. You will be able to optimize network communication and data management across major cloud platforms. Additionally, this book dives deep into these challenges, offering solutions such as multi-container Pods, advanced security techniques, and expert networking guidance. You will also explore persistent storage advancements, cloud-specific cluster management updates, and best practices for traffic routing. By the end of this comprehensive guide, you will possess the skills and knowledge to orchestrate your containerized applications with precision, ensuring their optimal performance and scalability. Stop settling for basic container management. Order your copy today and orchestrate your containers to greatness.
Includes bibliographical references and index
Keywords: Application software -- Development; Cloud computing; Open source software; Logiciels d'application; Développement; Logiciels libres